1994
DOI: 10.1016/s0022-5223(94)70007-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of canine allograft lung rejection by pulmonary lymphoscintigraphy

Abstract: We previously demonstrated that Iymphoscintigraphy could be used to study pulmonary lymphatic flow. RadiocoUoids, high-molecular-weight proteins tagged with radioactive markers, are injected percutaneously in the periphery of the lung. These molecules enter the lymph, are transported via lymphatic channels, and concentrate in the tributary hilar and mediastinal lymph nodes, where they can be visualized by nuclear scan. The goal of this study was to determine whether pulmonary Iymphoscintigraphy could be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The left lungs from donor iDTR VEGFR3-Cre ERT2 mice were transplanted into control littermates. Although lymphatic vessels were not surgically reconnected after lung transplantation, studies in mice and large animals have demonstrated that lymphatic drainage is reestablished 7-21 days after transplantation (33,48,49). We administered DT 21 days after transplantation of the iDTR VEGFR3Cre ERT2 lung to ensure that lymphatic function was first reestablished in the transplanted lungs ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The left lungs from donor iDTR VEGFR3-Cre ERT2 mice were transplanted into control littermates. Although lymphatic vessels were not surgically reconnected after lung transplantation, studies in mice and large animals have demonstrated that lymphatic drainage is reestablished 7-21 days after transplantation (33,48,49). We administered DT 21 days after transplantation of the iDTR VEGFR3Cre ERT2 lung to ensure that lymphatic function was first reestablished in the transplanted lungs ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Reestablishment of a lymphatic continuum after transplantation relies on formation of new lymphatic vessels (lymphangiogenesis), the exact roles of which remain enigmatic and somewhat controversial in transplant pathophysiology (10,11). While some studies have shown a beneficial role of lymphatic vessels in transplantation (12)(13)(14)(15), the prevailing view holds that they contribute to alloimmune responses that will result in the exacerbation of allograft rejection (16)(17)(18)(19). Therefore, it has been suggested that inhibiting lymphangiogenesis could be critical for graft tolerance and survival (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been suggested that inhibiting lymphangiogenesis could be critical for graft tolerance and survival (20,21). However, lung allografts are acutely rejected within 7 days after transplantation in animal transplant models (22)(23)(24)(25), whereas spontaneous restoration of lymphatic drainage from the transplanted lung to the lymph nodes occurs no earlier than day 7 after transplantation (26,27). Since the onset of lung rejection precedes the reestablishment of lymphatic continuity, it is possible that insufficient lymphatic drainage could be responsible, at least in part, for acute lung allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we strongly believe that lymphoid neogenesis is a stereotypic response of the immune system confronted with persistent antigenic stimulation in a tissue disconnected from the professional secondary lymphoid organs (6). While rejected grafts display an increased lymphatic density (as observed by the authors and others (3)), they are also characterized by reduced lymphatic outflow (7). This apparent discrepancy may be explained by the fact that the expansion of lymphatic network is orchestrated by activated B lymphocytes (8).…”
mentioning
confidence: 70%